Modern jurisprudence : a philosophical guide - Coyle, Sean (London [England] : Hart Publishing, 2022)
"This textbook presents a clear exploration of the historical developments and ideas that give modern thinking its distinctive shape. It guides students through the rival standpoints on jurisprudence from the origins of Western jurisprudential thought and the classical tradition to the emergence of 'modern' political thought. Chapters on Hart, Fuller, Rawls, Dworkin and Finnis lead the reader systematically through the terrain of modern legal philosophy, tracing the issues back to fundamental questions of philosophy, and indicating lines of criticism that result in a fresh and original perspective on the subject. The third edition includes a new chapter on feminist legal scholarship and non-Western approaches. Praise for the previous editions: 'An ideal starting place for anyone interested in, or studying, legal philosophy ... Its simple but ambitious aim to provide a concise and accessible guide is easily achieved.' (Student Law Journal) 'A decent choice for an introductory course on jurisprudence, or for a serious student who wishes to study on his or her own.' (Canadian Law Library)"--
1. Justice, Law and History Part One: Foundations -- 2. Origins of the Western Jurisprudential Tradition -- 3. Jurisprudence: The Classical Tradition -- 4. The Emergence of 'Modern' Political Thought -- 5. Images of Law from Grotius to Kant Part Two: Debates -- 6. Positive Law, Positive Justice: Hart -- 7. Justice in the 'Real World': Dworkin -- 8. Justice and the Liberal State: Rawls -- 9. Justice and the Common Good: Finnis -- 10. Justice and Legality: Fuller -- 11. Justice and Legal Order: Further Reflections Part Three: Critical Perspectives -- 12. Disruptive Theories -- 13. Conclusions?
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Jurisprudence -- History -- 20th century; Law -- Philosophy -- History -- 20th century; Electronic books